As reformas educacionais brasileiras: programas de ensino em Ciências e seriação escolar - Corrêa, Gilvane Gonçalves (1997)
The aim of this research was to analyze the main Brazilian educational reforms, which occurred between 1549 and 1996, and their contributions, at a broader level, to the regulation and political-pedagogical support of the serial curricular structure and, at a more restricted level, to the Teaching of Sciences. This study is organized as follows: Serial Education and Educational Institutions; The Brazilian School Seriation; Science Club - report of an experiment; Final considerations. The first chapter, 'Serial Education and Teaching Institutions', deals with the analysis and evolution of the historical context of the emergence to the current school model, the criteria used to promote the ordination and, later, the school grade itself. We also highlight the characteristics of relationships and educational institutions, demonstrating that they were constituted on hierarchical bases from the social hierarchy existing in each era, thus demonstrating the inseparable relationship that always existed between society and school and, therefore, between relationships. of teaching and social hierarchy. Social condition was crucial for access to school, which did not make it an option or an objective. The status conferred on those who obtained the knowledge was justified by their social status. The second chapter, ‘The Brazilian School Seriation ', deals with the moments of consolidation and evolution of the serial teaching mode through the legal regulation, as well as a comment about the alternative propositions to the school ranking after the Law 5692/71. In this chapter we make it clear that the serial teaching mode was consolidated in Brazil from the idealistic view of the world, present in both the Jesuit period and other reforms, culminating with Benjamin Constant (1890), which had all its principles founded. in the positivist aspect. This aspect has guided most of our educational policies and the school has sought to be true to its foundations, both in the organization and structuring of its knowledge. It works with the Inadmissibility of Contradiction, as if what took place within it was ahistorical and devoid of conflict, as if children and teachers and the whole community were not the result of relationships and multiple social and historical determinations. Didactically, we subdivided this chapter considering the chronological stages of the installation and consolidation of the serial teaching mode. They are: Educational Attempts: From the Jesuits the Preparatory Exams (1549 to 1889); The Benjamin Constant Reformation and Serial Education; From the Second Republic (1930 - 1937) to Law 4024/61; From Law 5692/71 and alternative proposals to school grade in Minas Gerais to 9394/96. In the third chapter, called ‘Science Club - Report of an Experience’, we narrate an experience lived by us as a Science teacher that meets a possible perspective of serial flexibility. In the Final Considerations we gather, in a single text, the conclusions about our object of study, which throughout the dissertation, were woven in detail in each chapter.